Prognostic Impact of High-Risk Pathologic Features in HPV-Related Oropharyngeal Squamous Cell Carcinoma and Tobacco Use. (May 2019) - Kompelli, Anvesh R.; Morgan, Patrick; Li, Hong; Harris, William; Day, Terry A.; Neskey, David M.
Objectives: To assess the impact of pathologic features and chronic tobacco use on human papillomavirus (HPV)–related oropharyngeal squamous cell carcinoma (OPSCC). Study Design: Case series with chart review. Setting: Single tertiary care referral center. Subject and Methods: A total of 301 patients were treated for OPSCC from 2008 to 2016. Clinical and pathologic T and N stage, American Joint Committee on Cancer (AJCC) stage (seventh and eighth edition staging manuals), cigarette pack years, alcohol use, and presence of extranodal extension (ENE), perineural invasion (PNI), or lymphovascular invasion (LVI) were assessed. Patients were stratified into HPV negative, HPV-positive heavy smokers (≥20 pack years), and HPV-positive nonsmokers. Five-year survival by Kaplan-Meier method was assessed. Results: Of the HPV-positive patients, 97 were nonsmokers and 73 were heavy smokers. HPV-positive heavy smokers had significantly decreased survival compared to their nonsmoking counterparts ( P = .02). The presence of ENE was associated with a significantly decreased 5-year survival ( P = .02) in heavy smokers relative to nonsmokers in HPV-positive patients. Furthermore, for the AJCC eighth edition, clinically stage 1 HPV-positive heavy smokers had significantly decreased survival relative to nonsmokers ( P = .01). Conclusions: This series highlights the potential need for more aggressive therapy for HPV-positive patients with extensive tobacco use under the new staging system.